Bivalent mRNA vaccine effectiveness against SARS-CoV-2 variants of concern - Monika Kumari; Shih-Chieh Su; Kang-Hao Liang; Hsiu-Ting Lin; Yu-Feng Lu; Kai-Chi Chen; Wan-Yu Chen; Han-Chung Wu (Journal of Biomedical Science, 2023)
Abstract Background Sequential infections with SARS-CoV-2 variants such as Alpha, Delta, Omicron and its sublineages may cause high morbidity, so it is necessary to develop vaccines that can protect against both wild-type (WT) virus and its variants. Mutations in SARS-CoV-2’s spike protein can easily alter viral transmission and vaccination effectiveness. Methods In this study, we designed full-length spike mRNAs for WT, Alpha, Delta, and BA.5 variants and integrated each into monovalent or bivalent mRNA-lipid nanoparticle vaccines. A pseudovirus neutralization assay was conducted on immunized mouse sera in order to examine the neutralizing potential of each vaccine. Results Monovalent mRNA vaccines were only effective against the same type of virus. Interestingly, monovalent BA.5 vaccination could neutralize BF.7 and BQ.1.1. Moreover, WT, Alpha, Delta, BA.5, and BF.7 pseudoviruses were broadly neutralized by bivalent mRNA vaccinations, such as BA.5 + WT, BA.5 + Alpha, and BA.5 + Delta. In particular, BA.5 + WT exhibited high neutralization against most variants of concern (VOCs) in a pseudovirus neutralization assay. Conclusions Our results show that combining two mRNA sequences may be an effective way to develop a broadly protective SARS-CoV-2 vaccine against a wide range of variant types. Importantly, we provide the optimal combination regimen and propose a strategy that may prove useful in combating future VOCs.